Optimalisasi Data Rambu Transportasi Darat Berbasis Web Maps - Khairil Hamdi; Yuhefizar, Yuhefizar (Prosiding SISFOTEK, 2023)
Traffic road equipment is an important component in supporting safety and smooth traffic. However, in reality, there is still a lot of road traffic equipment that is damaged and not maintained. This can endanger road users and potentially cause traffic accidents. Web maps are hosted maps usually used to display spatial information visually. Web maps can be created using various technologies, map APIs: Map APIs are a collection of functions that can be used to add maps to a website or application. online mapping software. The method chosen in this research is waterfall because each research step carried out must be sequential and structured to avoid the risk of errors in each sequence of processes carried out, maintenance of road traffic equipment needs to be carried out routinely and periodically to ensure its condition remains good and works fine. Maintenance can be done manually or using technology. Google Maps can be used to create traffic road equipment maps. These maps can be used to monitor the condition of traffic road equipment and to plan maintenance.